Ralações de gênero e poder nas polícias brasileiras: reflexos da dominação masculina estrutural - Goulart, Carolina (2023)
This dissertation investigates the incorporation of women in Brazilian police forces and the transformations social consequences caused by the performance of police activity by women, considering the gender equality as an essential requirement to guarantee human dignity in a society democratic. The question is whether the inclusion of women in Brazilian police forces has changed fact, power relations and, consequently, the organizational culture of domination masculine in these organs that constitute traditionally masculine spaces. Denouncing the oppressive hierarchy of domination from the perspective of the myth of supremacy masculine, we seek to establish the dimensions of power in relations between genders in these institutions, checking whether the presence of women in the Brazilian police structure has brought internal changes in these bodies, as well as changing social representations about the female exercise of police activity. The study reveals that, despite advances observed in the female trajectory, there still exist, informally, obstacles to greater presence of women in various sectors of police institutions, particularly in units specialized operations, and the power relations that are established are not always fair. Finally, it is discussed whether it is possible to overcome inequalities between genders and guarantee progress, giving up a predominantly masculine and patriarchal organizational culture, in order to allow equal conditions for both genders within police bodies. The proposal of research can contribute to expanding understanding of the challenges of police work feminine, praising differences in order to guarantee equal treatment. It is a qualitative research based on the deductive approach method. As for the technique of research, the methodology was characterized as bibliographic in the different disciplines to be treated and, regarding the procedure, the monograph was used. This research has as its milestones theorists power relations and gender equality.